BEING GRATEFUL AND ITS IMPACT ON THE LIFE QUALITY OF CANCER PATIENTS - Souza, Alvita (PEOPLE: International Journal of Social Sciences, 2019)
This study was designed to: (a) find out whether any relationship existed between the two variables of gratefulness and life quality, (b) develop an estimate of the direction and strength of the relationship which may exist between the two variables, and (c) examine the demographic variables contributing to Gratitude. Due to the critical condition of stage 3 and stage 4 cancer patients, the researcher selected stage 1 and stage 2 patients as they were in a better health condition which enabled them to be respondents. The total sample under study was 397 cancer patients in the age range of 30-67 years. Three scales were utilized that is the gratitude scale, the QLACS scale and EORTC for cancer patients. Results supported previous research that Being grateful positively correlated to Quality of life (r= .376, p=<0.05). The Mean and SD scores on Gratitude (M= 32.49& SD=3.48) and Quality of Life (M=252.74 & SD=34.46). Through multiple regression, females have contributed to 24% of the variance on gratitude which is significantly very high (t=6.69; P<0.001); further a high social support has contributed to 18.1% of the variance on gratitude which was significantly high (t=2.49; P<0.01). The implication of this study is that being grateful can be used as a significant feature to improve the life quality and bring forward a ray of hope particularly for those who are afflicted with the deadly disease of cancer.